“Sectual” Performance in Rule Texts - Miller, Shem (Dead Sea discoveries, 2018)
In this article, I examine descriptions of community meetings in Rule Texts to outline the content, authority, and functions of membership’s oral performance in the sectarian movement associated with the Dead Sea Scrolls. In particular, I explore portrayals of oral performance during local chapter meetings (1QS 6:1b–7a), nightly study sessions (1QS 6:7b–8a), general membership meetings (1QS 6:8b–13a; CD 14:3b–12a), covenant renewal ceremonies (1QS 1:24–26; CD 20:27–30), admission procedures (1QS 5:7c–9a, 6:13b–23; CD 15:5b–10a), and a meeting of Israel in the last days (1QSa 1:1–6a). Overall, I argue that oral performance consistently played a vital role in members’ lives, whenever and wherever they lived.